Sudden Cardiac Death Case with Massive Fibrosis in Heart in a 12 Years Old Boy - Türkmen, Nursel; Eren, Bülent; Fedakar, Recep; Aydıner, Hüsamettin; Erol, Oktan (The Bulletin of Legal Medicine, 2004)
Our case was 12 years old boy already dead during hospital admittance. He had been brought to the hospital after feehng suddenly sick while playing game. There was pin prick on the inner side of left nipple, and defibrilatör spoon marks on the anterior chest wall. In external examination on macroscopic autopsy investigation heart was found hypertrophic (390 g weight, right ventricle wall thickness: 0,7 cm., left ventricle wall thickness: 2,7 cm., septum thickness: 2 cm.). Chambers, leaflets and coronary artery lumina were normal on examination. On myocardial sections wide white areas on left ventricle wall were detected. There were nonspesific macroscopic findings in the other organs. Heart muscle fibers disappeared on wide areas, collogenous connecting tissue replaced, heart muscle fibers hypertrophic, lung emphysema, passive liver congestion, sple-enic paranchymal prominent hyperemia, focal bleeding had been investigated. On microscopic evaluation we aimed to discuss effect of fibrosis and cardiac failure findings of young hypertrophic hearts on sudden cardiac deaths in medicolegal aspects. Key words: Cardiac death, myocardial fibrosis, Adolescents.